The Effect of Perceived Value, Customer Trust, and Security on Customer Satisfaction in Online Two-Wheeled Transportation Services in Sukabumi - Dinda Nur Annisa; Rismawati; Endah Murtiana Sari (Universitas Sains Indonesia Publishing, 2026)
This study aims to analyze the influence of perceived value, customer trust, and security on customer satisfaction levels with online transportation services in Sukabumi. The study used a quantitative approach by distributing questionnaires to 200 online transportation users in Sukabumi. Data analysis included validity and reliability tests, classical assumption tests, partial T-tests, simultaneous F-tests, and coefficient of determination tests. The results showed that all three variables simultaneously had a significant effect on customer satisfaction. However, partially, only trust and security had a significant effect, while perceived value did not.